1991
DOI: 10.1080/02652039109374017
|View full text |Cite
|
Sign up to set email alerts
|

Formaldehyde content of milk in goats fed formaldehyde‐treated soybean oil‐meal

Abstract: Formaldehyde is used in ruminant feeding for different purposes including the protection of dietary proteins from ruminal degradation. The formaldehyde content of milk of goats fed various levels of formaldehyde-treated soybean oil-meal has been determined by using a sensitive HPLC method. Results showed a significant linear correlation between ingested formaldehyde and formaldehyde concentration in milk. About 0.02% of ingested formaldehyde was excreted in milk, as free formaldehyde.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 14 publications
2
4
0
Order By: Relevance
“…3 represent the experimentally obtained results of formaldehyde contents in pure (cow) milk, commercial UTH and powdered (cow) milk samples. The experimental results for pure cow milk (5.2 ± 3.5 ppm) were compatible with reported value (3.3 ppm) [30,33]. The experimental results show that formaldehyde content in UTH milk and powdered milk samples were higher (58.7-187.7 ppm) than that of pure milk sample.…”
Section: Naturally Occurring Formaldehyde Content In Fruits and Vegetsupporting
confidence: 90%
See 1 more Smart Citation
“…3 represent the experimentally obtained results of formaldehyde contents in pure (cow) milk, commercial UTH and powdered (cow) milk samples. The experimental results for pure cow milk (5.2 ± 3.5 ppm) were compatible with reported value (3.3 ppm) [30,33]. The experimental results show that formaldehyde content in UTH milk and powdered milk samples were higher (58.7-187.7 ppm) than that of pure milk sample.…”
Section: Naturally Occurring Formaldehyde Content In Fruits and Vegetsupporting
confidence: 90%
“…Values obtained for poultry (8.2 ± 1.0) and beef (8.5 ± 0.6) are slightly higher than the reported values, which are 2.5-5.7 and 4.6, respectively [30]. Generally formaldehyde is introduced in ruminant feeds either as a preservative agent or as a reagent used to dietary components from ruminal degradation [33]. It is reported that significantly higher concentration of formaldehyde was obtained from the fresh muscle tissue of calves consuming 0.10% formalin-treated whey, whereas the muscle tissue of controlled calves or those consuming whey containing 0.05% formalin exhibited lower formaldehyde concentration [37].…”
Section: Formaldehyde Content Of Milk Samplesmentioning
confidence: 83%
“…2 represent the formaldehyde contents found in pure cow milk sample and other UTH and powdered (cow) milk brands. The experimental results for pure cow milk (5.28±3.47ppm) was compatible with reported values (3.3 ppm) [23], [24]. The experimental results show that formaldehyde content in UTH milk and powdered milk samples were high compared to that of pure milk (58.79 to 187.75 ppm).The possible reason for higher formaldehyde content in commercial milk samples are dosing of formaldehyde during milk processing, preservation and/or packaging to improve the shelf life, or, conversion of milk ingredient to primary aldehyde during milk processing [25]- [27].…”
Section: A Naturally Occurring Formaldehyde Content Insupporting
confidence: 91%
“…However, pasture grass is characterized by its lushness of soluble N fermentable in the rumen resulting in a decrease in N retention. As a solution, the protection of proteins from microbial degradation in the rumen by chemical treatment was often used; however the use of formaldehyde is increasingly rejected because of the possible toxicity, indeed a positive correlation between oral administration of formaldehyde and its presence in the milk has been found on dairy cows and goats (Buckley et al, 1988;Barry and Tome, 1991). The protection of proteins by natural products like tannins present in local feed resources could increase the retention of N without negative repercussion (Terril et al, 1992).…”
Section: Introductionmentioning
confidence: 99%